Combined Corner‐Sharing and Edge‐Sharing Networks in Hybrid Nanocomposite with Unusual Lattice‐Oxygen Activation for Efficient Water Oxidation. (25th August 2022) - Zhang, Haijuan; Gao, Yongxin; Xu, Hengyue; Guan, Daqin; Hu, Zhiwei; Jing, Chao; Sha, Yuchen; Gu, Yuxing; Huang, Yu‐Cheng; Chang, Yu‐Chung; Pao, Chi‐Wen; Xu, Xiaomin; et al.
Abstract: Corner‐sharing and edge‐sharing networks are the two most important material genomes. Inspired by the efficient electron transport capacity of corner‐sharing structures and the low steric hindrance of edge‐sharing units, an attempt is made to exert both merits by combining these two networks. Here, a unique self‐assembled hybrid SrCo0.55 Fe0.5 O3‐ δ nanorod composed of a corner‐sharing SrCo0.5 Fe0.5 O3‐ δ phase and edge‐sharing Co3 O4 structure is synthesized through a Co‐site enrichment method, which exhibits the low overpotentials of 310 and 290 mV at 10 mA cm –2 for oxygen‐evolving reaction in 0.1 m and 1.0 m KOH, respectively. This efficiency is attributed to the high Co valence with strong CoO covalence and the short distance between CoCo/Fe metal active sites in hybrid nanorods, realizing a synergistic benefit. Combined multiple operando/ex situ characterizations and computational studies show that the edge‐sharing units in hybrid nanorods can help facilitate the deprotonation step of lattice oxygen mechanism (LOM) while the corner‐sharing motifs can accelerate the electron transport during LOM processes, triggering an unusual lattice‐oxygen activation. This methodology of combining important material structural genomes can offer meaningful insights and guidance for various catalytic applications. Abstract : Based on material structural genomes, a unique hybrid‐phase SrCo0.55 Fe0.5 O3‐ δ nanorod composed of corner‐sharing units (SrCo0.5 Fe0.5 O3‐ δ perovskite) with strong electron transport capacity and edge‐sharing motifs (Co3 O4 spinel) with low reaction steric hindrance by a self‐assembled Co‐site enrichment method are developed. SrCo0.55 Fe0.5 O3‐ δ nanorod exhibits efficient oxygen‐evolving performance with exceptional lattice oxygen activation.